Cardiovascular risk factors and not disease activity, severity or therapy associate with renal dysfunction in patients with rheumatoid arthritis. Issue 3 (10th March 2009) - Daoussis, D; Panoulas, V F; Antonopoulos, I; John, H; Toms, T E; Wong, P; Nightingale, P; Douglas, K M J; Kitas, G D
Abstract : Objectives: The present study aimed to evaluate the prevalence and associations of renal dysfunction in patients with rheumatoid arthritis (RA). It specifically addressed the hypotheses that renal dysfunction in these patients may associate with the presence of insulin resistance, dyslipidaemia, uric acid levels and/or current levels of systemic inflammation. Methods: Renal function was assessed by estimated glomerular filtration rate (GFR) using the modification of diet in renal disease equation in 400 consecutive RA patients for this cross-sectional, single-centre study. Risk factors for renal dysfunction were recorded/measured in all participants. Correlations between GFR and other variables were analysed by Pearson or Spearman test as appropriate. Linear regression was used to test the independence of the associations between GFR and other variables. Results: In this RA patient cohort, 67.75% of patients had a reduced GFR of less than 90 ml/minute per 1.73 m 2 and 12.75% had a GFR of less than 60 ml/minute per 1.73 m 2 . Multivariable analysis revealed significant associations between GFR and age (β = −0.370, p<0.001), female sex (β = −0.181, p=0.002), total cholesterol (β = −0.112, p=0.022), serum uric acid (SUA) (β = −0.425, p<0.001) and the presence of extra-articular disease, apart from sicca and/or nodules (β = −0.084, p=0.040). Conclusions: Renal dysfunction in RA is quite common and associates with classic cardiovascular risk factors such as advanced age and dyslipidaemia, levels of SUA and the presence of extra-articular disease. Renal dysfunction was not related to other RA-related factors including disease activity and duration, disability and past or present use of nephrotoxic medications.